2016
DOI: 10.1007/s10544-016-0137-0
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of fluids for multiphase drops-in-drops microfluidics

Abstract: This paper addresses the biocompatibility of fluids and surfactants in the context of microfluidics and more specifically in a drops-in-drops system for mammalian cell based drug screening. In the drops-in-drops approach, three immiscible fluids are used to manipulate the flow of aqueous microliter-sized drops; it enables merging of drops containing cells with drops containing drugs within a Teflon tube. Preliminary tests showed that a commonly-used fluid and surfactant combination resulted in significant vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…In typical UOMS cell culture, mineral (or paraffin) oil, silicone oil [i.e., pure linear PDMS polymer liquid (without small molecule additives and crosslinkers)], and fluorinated oil (i.e., perfluorocarbon liquid) are the three most commonly used oil types due to their overall biocompatibility. [ 37 ] However, in the context of gas permeability, the properties of oxygen solubility and diffusivity vary considerably among these oil types (Table 1 ). For instance, fluorinated oil has notably high oxygen solubility and diffusivity, and has been previously used as an oxygen carrier (i.e., to increase oxygen delivery) in cell culture.…”
Section: Resultsmentioning
confidence: 99%
“…In typical UOMS cell culture, mineral (or paraffin) oil, silicone oil [i.e., pure linear PDMS polymer liquid (without small molecule additives and crosslinkers)], and fluorinated oil (i.e., perfluorocarbon liquid) are the three most commonly used oil types due to their overall biocompatibility. [ 37 ] However, in the context of gas permeability, the properties of oxygen solubility and diffusivity vary considerably among these oil types (Table 1 ). For instance, fluorinated oil has notably high oxygen solubility and diffusivity, and has been previously used as an oxygen carrier (i.e., to increase oxygen delivery) in cell culture.…”
Section: Resultsmentioning
confidence: 99%
“…The second microdevice is made up of two layers of PDMS that have 3000 multi-level wells that allow a high droplet capture performance and an output channel to recover them. In addition, this double-layer design allows for greater gas exchange in conjunction with fluorinated oil (HFE-7500), which greatly helps cell viability [ 28 ].
Figure 2 Scheme of the microfluidic transfection system.
…”
Section: Resultsmentioning
confidence: 99%
“…In these systems, the oil is applied as a protective layer to prevent medium evaporation, maintain the pH and osmotic differences, as well as to protect from bacterial contaminations while keeping the system permeable to oxygen . Hexadecane as continuous oil phase has also proven to be noncytotoxic during the microfluidic encapsulation of different mammalian cells, where its contact with the cells is no longer than 4 h . In fact, the same study showed that mineral oil (which has very similar composition to paraffin oil) also proved to be noncytotoxic.…”
Section: Resultsmentioning
confidence: 99%